Smart Technology Effecting Tourism Development in Albania - MUÇA, Etleva; BOBOLI, Irena; KAPAJ, Ilir; KAPAJ MANE, Ana (Journal of Environmental Management and Tourism; Vol 13 No 8 (2022): JEMT, Volume XIII, Issue 8(64), Winter 2022DO - 10.14505/jemt.v13.8(64).04, 2022)
The concept of tourism represents a wide field of research and development, especially considering the global dimensions it is taking. In Albania, the tourism sector has become one of the most important sectors of economic development, especially in recent years when attention has increased in the international arena. The financial and social impact has begun to be experienced, when seeing that almost all figures in the tourism components show growth. The earthquake of November 26, 2019, and especially the isolation from the COVID-19 pandemic, had a negative impact, that limited the development and investment capacities in this sector. As a result of the great opportunities that our country offers in the field of tourism, technology has played a no less important role, especially for promotion to foreigners. The standardization of services has come as a result of awareness on development opportunities, but also as a result of constant demands and models borrowed from other countries, where digital transformation also undoubtedly plays a role. Another element affected in this study is the digitalization of business in the provision method of the tourism product. Specifically, tel_Albania, as a leading company in the country, has launched the tel_Business platform, by aiming to contribute to the fulfilment of the concepts of smart tourism and e-tourism.